Bibliometric analysis of the scientific production of an educational researcher affiliated with the National System of Researchers (Educational Knowledge, 2018)
This research article analyzes the scientific output of an educational researcher affiliated with the National System of Researchers of Mexico. It presents a descriptive study of the results obtained from a bibliometric analysis of the researcher's scientific production from 1991 to 2017. The analysis involved searches in various databases to locate articles, book chapters, and books in which the researcher is listed as author, co-author, or editor.The researcher's productivity was calculated according to document types (scientific/academic journals and publishers), output per year, country of publication, and the most frequent topics. The corpus consisted of 103 documents, of which 51 were academic/scientific articles, 23 were book chapters, and 29 were books. The results revealed the years of greatest productivity for the professor-researcher, with 2008, 2010, 2011, and 2016 having the highest publication rates, respectively. The journals and publishers most frequently used were Magistralis for articles, and GERNIKA and Trillas for book chapters and books. The most common topics addressed were related to Education, Ethics, and Values.
Keywords: Scientific production; professor researcher; bibliometric analysis; bibliometric indicators; education